The determinants of anti-diabetic medication adherence based on the experiences of patients with type 2 diabetes - Laleh Dehdari; Tahereh Dehdari (BMC, 2019)
Abstract Background The purpose of this study is to explain the experiences of patients with type 2 diabetes (T2DM) about medication adherence. Method A qualitative content analysis study was conducted at the Institute of Endocrinology and Metabolism Research and Training Center of Firoozgar Academic Hospital, affiliated to Iran University of Medical Sciences in Tehran, Iran during April-June 2017. Twenty-six semi-structured in-depth interviews were conducted with diabetic patients and their families. The participants were asked about their experiences of medication adherence. After the first round of the interviews, content analysis of data started and continued up to the data saturation. Results Four main themes including perceived barriers (with 6 subthemes including inadequate knowledge, situational influences, inadequate perceived threat about diabetes, treatment characteristics, personality traits and medication cost), perceived social support (with 3 subthemes including family, doctor and community supports), medication beliefs (with 3 subthemes including belief in the effectiveness of treatment, belief in the more effectiveness of complementary therapies than medication use and prioritizing the use of the pills instead of the insulin injection) and cues to action (with 2 subthemes including internal and external cues to action) emerged as the experiences of the participants in terms of anti-diabetic medications adherence which should be considered in developing medication adherence interventions for the patients with T2DM. Conclusion The patients with T2DM had more barriers for regular drugs consumption. They had incorrect beliefs about anti-diabetic drugs. In addition, they were in need of abroad support community, surroundings and also health professionals. Health systems should consider medication adherence training to be added to the treatment protocols of the diabetic patients.